2021
DOI: 10.1111/joim.13223
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine A plus low‐dose steroid treatment in COVID‐19 improves clinical outcomes in patients with moderate to severe disease: A pilot study

Abstract: Background COVID‐19 pandemic causes high global morbidity and mortality, and better medical treatments to reduce mortality are needed. Objective To determine the added benefit of Cyclosporine‐A (CsA), to low‐dose steroid treatment, in patients with COVID‐19. Methods Open‐label, non‐randomized pilot study of patients with confirmed infection of SARS‐CoV2, hospitalized from April to May 2020 at a single center in Puebla, Mexico. Comparative tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 57 publications
1
31
0
6
Order By: Relevance
“…A few small prospective studies at variable RoB evaluated mavrilimumab, 52 lenzilumab, 53 eculizumab, 54 sarilumab, 55 recombinant human IL-7 56 and the combination of ruxolitinib+eculizumab, 57 ruxolitinib+glucocorticoids 58 and cyclosporin+glucocorticoids. 59 However, none of them provided solid positive results.…”
Section: Resultsmentioning
confidence: 99%
“…A few small prospective studies at variable RoB evaluated mavrilimumab, 52 lenzilumab, 53 eculizumab, 54 sarilumab, 55 recombinant human IL-7 56 and the combination of ruxolitinib+eculizumab, 57 ruxolitinib+glucocorticoids 58 and cyclosporin+glucocorticoids. 59 However, none of them provided solid positive results.…”
Section: Resultsmentioning
confidence: 99%
“…Based on these two mechanisms, it has been suggested that CNIs could be used to treat COVID-19 (18). In fact, recent non-randomized studies suggest that cyclosporine could reduce mortality, mainly in patients with moderate to severe COVID-19 (19,20). Our study is the first RCT assessing the effect of corticosteroids plus a CNI (tacrolimus) in hospitalized patients with severe COVID-19.…”
Section: Introductionmentioning
confidence: 90%
“…In December 2019, a new type of human coronavirus (SARS-CoV-2), causing an emerging diseases (COVID- 19), was first recognized in China and spread globally (1,2). The COVID-19 was declared a pandemic by the WHO on March 12, 2020 (3), and it continues to spread worldwide, causing considerable morbimortality and economic damage.…”
Section: Introductionmentioning
confidence: 99%
“…J. L. G alvez-Romero 1 ; J. Deveaux-Homs 2 ; F. A. Real-Ram ırez 3 ; O. Palmeros-Rojas 4 & S. Pedraza-S anchez 5,6 From the 1…”
Section: Conflicts Of Interestunclassified
“…In response to the letter by Dr. Solanich and col., we acknowledge the authors for their comment about our recently published paper in Journal of Internal Medicine [1], on Cyclosporine plus steroids for COVID-19 treatment. Dr. Solanich and col. argue that it is unlikely that an in vivo antiviral effect of cyclosporine A (CsA) participates on the beneficial effects observed in our study on patients with COVID-19; their argument is based on a published paper showing that an in vitro concentration of 3.3 lM of CsA is necessary to reach LD50 of antiviral activity against SARS-CoV-2 tested on Vero cell cultures [2], which would be equivalent to 3968 ng/ml in plasma, representing 10 times the recommended clinical safe levels of CsA.…”
mentioning
confidence: 98%